Evaluación de la calidad seminal en equinos de raza criollo colombiano con tres diluyentes comerciales (2024)
This study tests three preservatives or diluents for equine semen which are Botusemen Gold from BotuPharma® Brazil laboratory, Ramp from Rampco® Colombia laboratory and Revolution from Incolamerica® United States, in three individuals with similar anatomical and physiological conditions of which the samples are prepared by a 1/1 dilution and then initial characteristics such as color, pH, sperm malformations are evaluated followed by evaluation using a neubauer chamber to determine the percentage of total motility and progressive motility in an initial control of twelve hours followed by controls at intervals of twenty-five hours, pH, sperm malformations followed by evaluation using the neubauer chamber to determine the percentage of total motility and progressive motility in an initial control of twelve hours followed by controls at twenty-four hour intervals, storing them in a medium of 2-8° in order to determine and analyze which product is better or retains the best characteristics under these conditions and why.